Developing a Theoretical Direction for In-Service Education Using Locsin’s TCCN Theory in Psychiatric Nursing - Takashima, Yoshiyuki; Soriano, Krishan; Onishi, Kaito; Gil, Soriano; Osaka, Kyoko; Kataoka, Mutsuko; Yasuhara, Yuko; Schoenhofer, Savina; Tanioka, Tetsuya (Celebes Nursing Journal, 2025)
Introduction: There is a pressing need to improve psychiatric nursing services by bridging the gap between technological competency and ethical, compassionate care. Objective: This study aimed to develop and propose a structured in-service education program for psychiatric nurses, grounded in Locsin’s Technological Competency as Caring in Nursing (TCCN) theory. Methods: The program was developed using the Analyze, Design, Develop, Implement, and Evaluate (ADDIE) model. The proposed in-service education program consists of ten structured sessions, which are aligned with Locsin's five assumptions and three nursing processes. The planned evaluation includes participant reports and the use of the Technological Competency as Caring in Psychiatric Nursing Instrument (TCCNPNI), which assesses nurses' perceptions of their technological competency. This instrument allows for pre- and post-evaluations to determine the program's effectiveness. This education plan, rooted in TCCN theory, addresses the unique needs of psychiatric nurses working with vulnerable populations. Results: The anticipated outcomes highlight the potential of technology to enhance patient care quality and dignity in psychiatric settings. As technology becomes more integral to psychiatric nursing practice, nurses must not only develop technical competence but also uphold ethical sensitivity. Conclusion: This program provides a structured approach to achieving these competencies through continuing education.